The Effect of Leadership Style on Employee Work Discipline in the Lebakwangi District Office - Bekti, Herijanto (SEAN Institute, 2023)
In the Lebakwangi District Office, the purpose of this study is to investigate how different styles of leadership influence the level of employee work discipline. In order to achieve high levels of efficiency and productivity in the working environment, work discipline is an essential component that must be present. In the meanwhile, a leadership style that is effective can help to build a culture inside a company that is conducive to good work discipline. This study takes a quantitative approach and employs the survey method in its data collection. According to the findings of this research project, the work discipline of employees working in the Lebakwangi subdistrict office is impacted by the leadership style of their superiors. It is believed that the findings of this research will be able to provide management and leaders in the Lebakwangi District Office with recommendations that will assist in enhancing employee work discipline by increasing the number of successful leadership styles. The repercussions of this study are anticipated to provide a constructive contribution to efforts to increase the level of organizational performance and to realize the objectives that have been established.